Community acceptance of environmental larviciding against malaria with Bacillus thuringiensis israelensis in rural Burkina Faso – A knowledge, attitudes and practices study. Issue 1 (1st January 2021) - Dambach, Peter; Traoré, Issouf; Sawadogo, Hélène; Zabré, Pascal; Shukla, Sharvari; Sauerborn, Rainer; Becker, Norbert; Phalkey, Revati
ABSTRACT: Background: Malaria control is based on early treatment of cases and on vector control. The current measures for malaria vector control in Africa are mainly based on long-lasting insecticidal nets (LLINs) and to a much smaller extent on indoor residual spraying (IRS). While bed net use is widely distributed and its role is intensively researched, Bti-based larviciding is a relatively novel tool in Africa. In this study, we analyze the perception and acceptability of Bti-based larval source management under different larviciding scenarios that were performed in a health district in Burkina Faso. Objective: To research people's perception and acceptance regarding biological larviciding interventions against malaria in their communities. Methods: A cross-sectional study was undertaken using a total of 634 administered questionnaires. Data were collected in a total of 36 rural villages and in seven town quarters of the semi-urban town of Nouna. Results: Respondents had basic to good knowledge regarding malaria transmission and how to protect oneself against it. More than 90% reported sleeping under a bed net, while other measures such as mosquito coils and insecticides were only used by a minority. The majority of community members reported high perceived reductions in mosquito abundance and the number of malaria episodes. There was a high willingness to contribute financially to larviciding interventions among interviewees. Conclusions: This study showed that biological larviciding interventions are welcomed by the population that they are regarded as an effective and safe means to reduce mosquito abundance and malaria transmission. A routine implementation would, despite low intervention costs, require community ownership and contribution.